Specialized Health Courts for National Health Insurance Disputes in Indonesia - Siradj Okta; Dedy Yudhistira; Nugroho Adipradana; Fachrudin Sembiring; Kris Tumbel (LOCUS MEDIA PUBLISHING, 2026)
Indonesia's National Health Insurance (Jaminan Kesehatan Nasional, JKN) has integrated healthcare financing and administration into a single national system, yet the institutions responsible for resolving healthcare disputes remain divided across multiple jurisdictions. This institutional divergence has become increasingly significant as healthcare disputes now extend beyond medical negligence and insurance reimbursement to encompass administrative decision-making, contractual relationships, professional accountability, and the constitutional right to health. This article examines whether Indonesia's existing judicial framework remains capable of adjudicating disputes generated by an integrated healthcare system. It first analyses the legal characteristics of disputes arising under JKN and the fragmentation of their resolution across existing institutions. It then evaluates the institutional limitations of the current framework through doctrinal and comparative legal analysis. The article argues that the principal challenge lies not in the absence of legal remedies but in the allocation of adjudicatory jurisdiction. Although existing institutions perform legitimate statutory functions, no single forum possesses the institutional capacity to resolve the interconnected legal and technical issues presented by contemporary healthcare disputes. It concludes that a specialized health court represents a constitutionally compatible institutional response to the evolving demands of Indonesia's healthcare governance and access to justice.